IMPROVED NON-LINEAR SIGNAL ESTIMATION TECHNIQUE FOR UNDERSEA SONAR BASED NAVAL APPLICATIONS - JAWAHAR A; VISHNU CHAKRAVARTHI CH (Innovare Journal of Engineering and Technology, 2016)
The aim of this work is to develop passive target tracking algorithm, suitable for implementation in target motion analysis for underwater applications. The vehicle is assumed to be standstill in underwater watching for any target ship using bearings only measurements. Using these measurements, the algorithm calculates the course of the target, which is further used to find out target range and speed. Provision is given to generate range and course if the speed of the target is known by some other means. Pseudo Linear Estimator (PLE) is developed to reduce the noise in the measurements and to find out target motion parameters. Though PLE offers a biased estimate in certain scenarios, it has an advantage as it hardly diverges. It offers the features of Kalman filter viz., sequential processing, flexibility to adopt the variance of each measurement etc.Â The Monte-Carlo simulation results are presented for a typical scenario and it is shown that this algorithm is useful for naval underwater applications.Â